Gelatin films dendronized selectively on one side. Enhancing antimicrobial properties and water repellence - García Schejtman, Sergio Davi (2015)
To develop a material with potential biomedical applications, novelgelatin films were prepared by cold-casting method using cerium(III) and genipinsolution as cross-linking agents, and surface modified with dendritic molecules. Thestructure and properties of the synthesized gelatin films were investigated by ATRFTIR,mechanical tests, swelling behavior and water vapor permeability (WVP).The results showed that cross-linking could improve the mechanical and microbiologicalproperties and lower the hydrophilic property of gelatin films. According toATR-FTIR analysis, it can be concluded that the dendronization took place on onlyone of the faces of the films. The results have shown that the experimentalmethodology performed allows one-surface modification, so a novel biomaterialwas obtained in the form of a film with good properties and dendritic structure inone face (hydrophobic and hydrophilic faces), rendering a multivalent structureuseful in biomedicine development.